ARAB SUNNI DAN IRAN SYI`AH KONTEMPORER: KONFLIK ATAU PERSAINGAN? - MUHAMMAD MUTAWALI (FiTUA: Jurnal Studi Islam, 2020)
This article explains the problems that occur between Sunni and Shi'a schools starting after the death of the Prophet Muhammad. History records that there has been a prolonged conflict which is motivated by political conflict, ideological conflict, paradigm conflict and thought which are factors that hamper reconciliation efforts, given the existence of very painful past events between the two streams. For Shiites, the story of discrimination experienced by Ali ibn Abi Talib until the tragedy of Karbala with the killing of Husein the Prophet's grandson and the story of the Ahlul Bait pain became a very painful social memory. For Sunnis, insults, insults, curses and disbelief aimed at the main Companions of Abubakar, Umar, Uthman and the wife of Rasulullah Aisyah Al-Kubra became the main cause of disharmony in relations between Sunnis and Shiites. Disharmonization has also impacted on relations between countries in the Middle East who competed for influence in the Gulf until now after the Arab Spring.